1972
DOI: 10.1073/pnas.69.8.2145
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-sensitive adenylate cyclase in caudate nucleus of rat brain, and its similarity to the “dopamine receptor”

Abstract: An adenylate cyclase that is activated specifically by low concentrations of dopamine has been demonstrated in homogenates of caudate nucleus of rat brain. A half-maximal increase in the activity of the enzyme occurred in the presence of 4 ,M dopamine. Concentrations of dopamine as low as 0.3 MAM stimulated the activity of the enzyme. The adenylate cyclase activity of the homogenates was also stimulated by low concentrations of apomorphine, a substance known to mimic the physiological and pharmacological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
199
0
5

Year Published

1973
1973
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 819 publications
(209 citation statements)
references
References 15 publications
5
199
0
5
Order By: Relevance
“…Amphetamine, an indirect dopaminergic agonist, decreases PPI via dopamine D2 receptors (Ralph-Williams et al, 2002) that inhibit AC activity (Neves et al, 2002). Conversely, haloperidol, a typical antipsychotic that blocks D2 receptors (cf., Miyamoto et al, 2005) and increases cAMP signaling in forebrain structures (Berndt and Schwabe, 1973;Kaneko et al, 1992;Kaplan et al, 1999;Dwivedi et al, 2002; but see Kebabian et al, 1972;Carenzi et al, 1975), increases PPI (Ouagazzal et al, 2001). Thus, there appears to be a relationship between cAMP and PPI levels.…”
Section: Introductionmentioning
confidence: 97%
“…Amphetamine, an indirect dopaminergic agonist, decreases PPI via dopamine D2 receptors (Ralph-Williams et al, 2002) that inhibit AC activity (Neves et al, 2002). Conversely, haloperidol, a typical antipsychotic that blocks D2 receptors (cf., Miyamoto et al, 2005) and increases cAMP signaling in forebrain structures (Berndt and Schwabe, 1973;Kaneko et al, 1992;Kaplan et al, 1999;Dwivedi et al, 2002; but see Kebabian et al, 1972;Carenzi et al, 1975), increases PPI (Ouagazzal et al, 2001). Thus, there appears to be a relationship between cAMP and PPI levels.…”
Section: Introductionmentioning
confidence: 97%
“…Activation of muscarinic receptors on BLA projection neurons influences membrane-bound ion channels, changing their sodium and potassium conductance and, thus, depolarizing the neurons (Yajeya et al 1999). Although activation of DA receptors in other brain regions including the striatum works through changes in adenylyl cyclase activity (Kebabian et al 1972), recent evidence suggests that activation of D1 receptors in the BLA does not affect levels of cAMP, phospholipase C, or intracellular calcium (Leonard et al 2003;Loretan et al 2004). Instead, it appears that D1 receptors work through Src, a family of nonreceptor tyrosine kinases, to produce activity changes in BLA interneurons (Loretan et al 2004), though it is unknown whether D1 receptor activation in projection neurons modulates Src or by what mechanism D2 receptor activation influences input resistance.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the non-selective dopamine agonist apomorphine was suggested to have sufficient dopamine D, agonistic activity to ameliorate the symptoms of parkinsonism in the primate model under blockade of its D2 agonist action, in contrast to SKF 38393 which deteriorated the parkinsonism (7), although apomorphine has been reported to exhibit a partial dopamine D1 agonistic activity in the adenylate cyclase assay of rat striatal homogenates, like SKF 38393 (19). These discrepancies may be due to following: The dopamine D1-receptor family, which is composed of DIA-and DIB-receptor subtypes, is coupled to the stimulation of adenylate cyclase, but the conventional assay for the adenylate cyclase can not detect differentially the intrinsic activity of some ligands on each subtype; and as a result, it is difficult at present to say whether apomorphine and SKF 38393 may act as a full or a partial agonist (possibly antagonist) to the DIAand DIB-receptor subtypes, although they may bind with a high affinity to both subtypes (2).…”
Section: Discussionmentioning
confidence: 88%